(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1863)
An account of the life of Sir Peter Young and his family. His working life as a tutor to James VI & I, and his appointment as ambassador to Denmark on three occasions are also mentioned. Several letters from Young to Sir Patrick Vans of Barnbarroch, who accompanied him as an ambassador to Denmark, are then transcribed.